“Diseño de la gestión integral de residuos sólidos en el cantón Quinsaloma, provincia de Los Ríos” - Yunda Álvarez, Franklin Ernesto (2020)
The canton of Quinsaloma belongs to the province of Los Ríos and is known for its diverse agricultural activities. Currently, solid waste management only includes collection, transportation, and final disposal. The lack of temporary storage containers makes it difficult for people to find a suitable place to dispose of their waste; in the rural zone, 30% of the municipalities do not have collection services, causing people to dispose of their waste in abandoned lots or incinerate it in the open air. Diagnosing the current situation of solid waste management, optimizing the collection system through the implementation of temporary storage containers, and proposing the optimal site for the location of a sanitary landfill are the objectives of the research. A survey of 354 inhabitants was carried out through the implementation of a questionnaire consisting of 2 sections of questions: demographic information and solid waste management phases. The survey revealed that 60.5% of the population does not know how their waste is handled; however, 89% of those questioned believe that the accumulation of waste contributes to the proliferation of pests, bad odors and diseases. The application of the questionnaire showed that plastic bags are the most common material used to store waste. The generation of solid waste in the canton of Quinsaloma amounts to 270 tons per month, of which 80.2% of the people deliver their waste to the collection truck. Tukey's statistical test showed that there are significant differences in the means as a result of the variability of responses to the questions posed to the respondents. Through daily trips in the collection truck, information was collected on the current collection route and a proposal was made for a new collection route complemented with the implementation of temporary storage containers, whose route is composed of four routes, one for the urban area and three routes for the rural area with morning and evening collection schedules. The canton does not have its own sanitary landfill, which is why an integrative proposal was made through the identification of the optimal site for the location of a sanitary landfill, through a multi-criteria analysis with the use of Geographic Information Systems, two optimal areas were determined, one of 62.39 ha and the second of 255.11 ha. Keywords: Geographic Information Systems, Sanitary Landfill, Integrated Solid Waste Management